Operasi katarak traumatika dengan pemasangan lensa intraokuli pada anak - Wasisdi Gunawan, Wasisdi Gunawan (Universitas Gadjah Mada, 1996)
In traumatic cataract extraction it is often difficult to assess the result of the operation and the recovery of the visual acuity because there are many complications and recurrence of the previous uveitis.The purpose of this study is to evaluate the visual function improvement and many influencing factors after extraction of traumatic cataract with intraocular lens implantations in children.Eleven cases of posterior chamber intraocular lens implantations in cataract traumatic children were reported in Dr Sardjito General Hospital between 1990 and 1995.There were 10 boys and 1 girl. The mean age was 8 years ranging from 3 years to 14 years. The visual acuity improvement occurred in 10 cases and in 1 case the visual acuity remained stable. Five cases had post traumatic uveitis that reccurred after cataract extractions and IOL implantation and 1 patient showed retinal cicatrization identified after the operation.Key words: traumatic cataract - traumatic uveitis - intra ocular lens implantation - retinal cicatrization -Â visual acuity recovery